The Effect of the TGT Cooperative Learning Model Assisted by Snakes and Ladders on the Mathematics Learning Outcomes of Second Grade Students - Damanik, Jenemy Amelya; Sipayung, Regina; Tanjung, Darinda Sofia; Gaol, Rumiris Lumban; Pinem, Irmina; Rajesh, Viji (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This research aims to determine the effect of variable X, namely the TGT cooperative learning model assisted by a snakes and ladders game, on variable Y, namely the mathematics learning outcomes of second-grade students at SD Negeri 104276 Pulau Tagor in the 2024/2025 academic year. The background of this study is the low learning outcomes of students in multiplication material due to the dominance of the lecture method and the lack of use of interesting learning media. The method used is the experimental method with a One Group Pretest-Posttest Design. There were 28 students as research subjects. The instrument used was a learning outcome test to determine the changes before and after the treatment. The pretest results showed that the average student score was 59.57 with a mastery level of only 39.28% or 11 out of 28 students. After implementing the TGT learning model assisted by snakes and ladders, the posttest results increased significantly with an average score of 81.25 and a mastery level of 89.29% or 25 out of 28 students. Thus, there was an increase in learning mastery of 50.01%. Based on the results of the research calculations, it shows that there is an effect of the Team Games Tournament Cooperative Learning Model Assisted by a Snake and Ladder Board Game on the mathematics learning outcomes of Grade II students at SD Negeri 104276 Pulau Tagor in the 2024/ 2025, where rhitung ≥ rtabel, namely 0.927 ≥ 0.373, there is a high effect, and thitung ≥ ttabel, where thitung 6.518 ≥ ttabel 2.064 at a significance level of α = 0.05. Thus, Ha is accepted and Ho is rejected. Therefore, it can be concluded that there is a significant effect between the use of the TGT cooperative learning model assisted by snakes and ladders (variable X) on improving students' mathematics learning outcomes (variable Y).